2016
DOI: 10.1063/1.4943776
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanisms of cation injection in conducting bridge memories: The case of HfO2 in contact with noble metal anodes (Au, Cu, Ag)

Abstract: Resistance switching is studied in HfO2 as a function of the anode metal (Au, Cu, and Ag) in view of its application to resistive memories (resistive random access memories, RRAM). Current-voltage (I-V) and current-time (I-t) characteristics are presented. For Au anodes, resistance transition is controlled by oxygen vacancies (oxygen-based resistive random access memory, OxRRAM). For Ag anodes, resistance switching is governed by cation injection (Conducting Bridge random access memory, CBRAM). Cu anodes lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 48 publications
9
43
0
Order By: Relevance
“…This is the forming process, during which conductive paths are created through the insulating dielectric layer. It is triggered by the forming voltage (V f ), equal to 3.3 V. The current increase at lower voltages is probably due to preliminary redox or diffusion phenomena [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the forming process, during which conductive paths are created through the insulating dielectric layer. It is triggered by the forming voltage (V f ), equal to 3.3 V. The current increase at lower voltages is probably due to preliminary redox or diffusion phenomena [20].…”
Section: Methodsmentioning
confidence: 99%
“…Positively biasing this active electrode, oxygen migration, probably in the O 2− form, is enhanced leading to a further reduction of the Al 2 O 3 and an increase of the AlO x contribution (+3.3%). Oxygen migration creates positively charged V O in the alumina, which may have an important role in the formation of conductive filaments by acting as easy ionic diffusion paths in the solid electrolyte [20,22,23].…”
Section: Hard X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…For instance, the electroforming process for the valence change memory (VCM) based bipolar devices may be polarity dependent due to the built-in asymmetry of the contacts at the top and bottom electrode interfaces as determined by the device design and fabrication procedure 33 . In the case of chemical metallization memory (ECM) 34,35 based devices, the formation of a filament requires the electrochemical dissolution of an active electrode (usually Ag or Cu), followed by the drift of the injected metal cation clusters toward the counter electrode by a positive voltage applied to the active electrode 26,36,37 . Thus, the comparison of the response of these devices to different biasing schemes may provide valuable information for deciphering the nature of resistive switching in a material system.…”
Section: Electrical Characterizationmentioning
confidence: 99%
“…The electrodes employed in memristor-based electronic devices may significantly affect the resistive switching (RS) behavior. For metal-oxide thin-film systems that make use of inert metals as electrodes, the switching mode is mostly bipolar [24][25][26][27][28] , although unipolar operation characteristics have also been demonstrated 18 . In some cases, the mode of operation could be changed between bipolar and unipolar by adjusting the operation conditions 29 or by introducing and tuning the thickness of an oxygen scavenging metal layer 30 .…”
mentioning
confidence: 99%
“…[4][5][6] Today, even flash memory has not been able to combine all of these features, especially in terms of writing speed. [23][24][25][26] Nevertheless, to our knowledge, the equilibrium between metal ions and oxygen vacancies dependence on the chosen material and its impact on device performances has never been investigated. For the former, studies have shown the ability of RRAM to operate at sub-µA, [7] while novel integration solutions such as passive crossbars [8] and 3D stacking have been proposed to overcome www.advelectronicmat.de it appeared that material properties such as energy migration barrier of species composing switching filament is linked to HRRAM behavior.…”
Section: Introductionmentioning
confidence: 99%